2011
DOI: 10.1016/j.meatsci.2011.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Muscle fiber type characterization and myosin heavy chain (MyHC) isoform expression in Mediterranean buffaloes

Abstract: This study aimed to evaluate myosin heavy chain (MyHC) isoform expression and muscle fiber types of Longissimus dorsi (LD) and Semitendinosus (ST) in Mediterranean buffaloes and possible fibers muscles modulation according to different slaughter weights. The presence of MyHC IIb isoforms was not found. Only three isoforms of MyHC (IIa, IIx/d and I) were observed and their percentages did not vary significantly among slaughter weights. The confirmation of the presence of hybrid muscles fibers (IIA/X) in LD and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 27 publications
(36 reference statements)
1
4
0
1
Order By: Relevance
“…The speed of contraction increases in the rank order I <IIa <IIx <IIb [23]. Previous studies revealed variation in the type of fibers and myosin isoforms present in Longissimus dorsi and Semitendinosus muscles in buffalo [24]. In the present study, myosin heavy chain 2 (MYH2 or MyHC IIa) was up-regulated in flank steaks compared with tenderloin steaks in Simmental cattle.…”
Section: Discussionsupporting
confidence: 48%
“…The speed of contraction increases in the rank order I <IIa <IIx <IIb [23]. Previous studies revealed variation in the type of fibers and myosin isoforms present in Longissimus dorsi and Semitendinosus muscles in buffalo [24]. In the present study, myosin heavy chain 2 (MYH2 or MyHC IIa) was up-regulated in flank steaks compared with tenderloin steaks in Simmental cattle.…”
Section: Discussionsupporting
confidence: 48%
“…Slow muscle fiber types qualify for resistance to gravity and fatigue and express MHC-I and different proportions of MHC-IIa. Fast fiber types that can be easily fatigued, maintain body movement and intensive activities mainly express MHC-IIb and MHC-IIx [6,7,8]. Moran et al showed that the myosin binding dynamics are altered in ovariectomized mice, leading to a reduction in titanic force that is restorable by E 2 replacement [9].…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal muscle fibers are generally divided into four types according to the myosin heavy chain ( MyHC ) isoforms, namely, types I, IIA, IIB, and IIX [ 70 ]. However, there are very few type IIX muscle fibers in poultry skeletal muscle [ 71 ].…”
Section: Discussionmentioning
confidence: 99%